Manajemen Program Traveling and Teaching dan Smart Center Komunitas 1000 Guru Malang dalam Peningkatan Mutu Sekolah - Asriadi Asriadi; Ahmad Yusuf Sobri; Sultoni Sultoni (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This research described about the management program of traveling and teaching, also the smart center of 1000 Guru Malang community in enhancing the quality of the schools. Traveling and teaching program was a social event in learning aspects that was carrying out the concept of fun learning in primary school and giving donation through traveling and giving, while the smart center was continuity event and or long term program that was focus on giving direct assistance whether physical and non-physical assistance in 12 months. The researcher used qualitative research design by using multi-sites research design. The result of the management programs that was consisting of planning, implementing, and evaluating that was done by the 1000 Guru Malang community showed that the indicators of the achievement school's quality that was consisting of enhancing the society's participation, academical and non-academical achievements, school image in the society, and the quality of school facilities.Abstrak: Penelitian ini mendeskripsikan manajemen program traveling and teaching dan smart center komunitas 1000 Guru Malang dalam peningkatan mutu sekolah. Program traveling and teaching merupakan kegiatan sosial di bidang pendidikan yang mengusung konsep pembelajaran menyenangkan di sekolah dasar dan pembagian donasi yang dikemas melalui penjelajahan sambil berbagi. Smart center merupakan kegiatan lanjutan dan atau program jangka panjang yang fokus pada pemberian bantuan langsung ke sekolah baik secara fisik maupun non fisik dalam jangka waktu 12 bulan. Peneliti menggunakan pendekatan kualitatif dengan jenis rancangan studi multi situs. Hasil penelitian menunjukkan bahwa manajemen program yang terdiri dari perencanaan, pelaksanaan, dan evaluasi yang dilaksanakan komunitas 1000 Guru Malang menunjukkan indikator pencapaian mutu sekolah yang meliputi peningkatan partisipasi masyarakat, prestasi akademik dan non akademik, citra sekolah di masyarakat, dan kualitas fasilitas sekolah.